Arms control and disarmament in Southern Africa: An assessment of civil society and state responses in Mozambique 1995 – 2003 - Henda, Mongi Stanley (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MA (Political Science))--University of Stellenbosch, 2010.